Characterization of mixed DODAB/monoolein aggregates using Nile Red as a solvatochromic and anisotropy fluorescent probe - Silva, J. P. Neves (2009)
The aim of this study was to get a further knowledge of the interactions between lamellar and non-lamellar forming-phospholipids, as a tool to better understand the membrane dynamics and function. We have studied the behaviour of aqueous mixtures of a cationic lipid (dioctadecyldimethylammonium bromide) and a neutral phospholipid (1-monoolein) in 10 to 150 micro molar total lipid concentration range. The effect of 1-monoolein on the physical properties (microviscosity, hydration and polarity) of the self-organized mixed aggregates was accessed by studying the steady-state fluorescence emission and anisotropy of the dye Nile Red. This information was combined with 90º Static Light Scattering assays in order to detect any structural variations in these vesicle systems. The results were interpreted by the coexistence of vesicular structures and other aggregates probably with a bicontinuous nature.